2022
DOI: 10.3389/fcimb.2022.797017
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Two Strains of Prototheca wickerhamii Provide Insight Into the Protothecosis Evolution

Abstract: The Prototheca alga is the only chlorophyte known to be involved in a series of clinically relevant opportunistic infections in humans and animals, namely, protothecosis. Most pathogenic cases in humans are caused by Prototheca wickerhamii. In order to investigate the evolution of Prototheca and the genetic basis for its pathogenicity, the genomes of two P. wickerhamii strains S1 and S931 were sequenced using Nanopore long-read and Illumina short-read technologies. The mitochondrial, plastid, and nuclear genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This was also true for the DEPs and metabolites (Figure 2A). This is consistent with previous results showing that strains HN01 and ATCC16529 evolved closely (Guo et al, 2022). Interestingly, we found that mannan endo-1,4-b-mannosidase was significantly downregulated in S1 compared to that in HN01 (Figure 2B).…”
Section: Bioinformatics Analysis and Interpretation Of Morphological ...supporting
confidence: 93%
See 3 more Smart Citations
“…This was also true for the DEPs and metabolites (Figure 2A). This is consistent with previous results showing that strains HN01 and ATCC16529 evolved closely (Guo et al, 2022). Interestingly, we found that mannan endo-1,4-b-mannosidase was significantly downregulated in S1 compared to that in HN01 (Figure 2B).…”
Section: Bioinformatics Analysis and Interpretation Of Morphological ...supporting
confidence: 93%
“…Moreover, higher temperatures combined with high humidity would enhance the growth of P. wickerhamii in the environment (Jagielski et al, 2022). This study provides an indepth understanding of the genome sequences of different strains of P. wickerhamii isolated from clinical specimens, contributes to a basic understanding of this alga, and explores future prevention and treatment strategies (Guo et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Close relatedness between organisms exhibiting vastly different lifestyles is often a hallmark of complex and captivating evolutionary paths, and a perfect example of that can be found among the green algal order Chlorellales. The relatives of the model green microalga Chlorella include a photosynthetic genus Auxenochlorella, as well as two secondarily non-photosynthetic genera -Helicosporidium, which are highly specialized, obligate gut parasites of insects (de Koning and Keeling, 2006;De Koning and Keeling, 2004;Sun and Pombert, 2014;Tartar, 2013), and Prototheca, which are predominantly free-living opportunistic pathogens of diverse vertebrates, including humans (Borza et al, 2005;Guo et al, 2022;Jagielski et al, 2019Jagielski et al, , 2018. The evolutionary past of these organisms, especially their transitions between photosynthetic, parasitic and free-living heterotrophic lifestyles, remains mysterious even with the availability of several genomic datasets.…”
Section: Introductionmentioning
confidence: 99%